What do premiums paid for bank M&As reflect? The case of the European Union - Hagendorff, Jens; Hernando, Ignacio; Nieto, Maria J.; Wall, Larry D. (Journal of Banking & Finance, 2012)
We analyze the takeover premiums paid for a sample of domestic and cross-border bank takeovers in the European Union between 1997 and 2007. We find that acquiring banks value profitable, high-growth and low risk targets. We also find that the strength of bank regulation and supervision as well as deposit insurance regimes in Europe have measurable effects on takeover pricing. Stricter bank regulatory regimes and stronger deposit insurance schemes lower the takeover premiums paid by acquiring banks. This result, presumably in anticipation of higher compliance costs, is driven by domestic deals. Similar qualitative results are found for both the entire sample and the sample of publicly traded targets.